Drug Targeting via Platelet Membrane–Coated Nanoparticles. Issue 1 (9th September 2020) - Wang, Shuyan; Duan, Yaou; Zhang, Qiangzhe; Komarla, Anvita; Gong, Hua; Gao, Weiwei; Zhang, Liangfang
Abstract : Platelets exhibit distinct surface moieties responsible for modulating their adhesion to various disease‐relevant substrates involving vascular damage, immune evasion, and pathogen interactions. Such broad biointerfacing capabilities of platelets have inspired the development of platelet‐mimicking drug carriers that preferentially target drug payloads to disease sites for enhanced therapeutic efficacy. Among these carriers, platelet membrane–coated nanoparticles (denoted "PNPs") made by cloaking synthetic substrates with the plasma membrane of platelets have emerged recently. Their "top‐down" design combines the functionalities of natural platelet membrane and the engineering flexibility of synthetic nanomaterials, which together create synergy for effective drug delivery and novel therapeutics. Herein, the recent progress of engineering PNPs with different structures for targeted drug delivery is reviewed, focusing on three areas, including targeting injured blood vessels to treat vascular diseases, targeting cancer cells for cancer treatment and detection, and targeting drug‐resistant bacteria to treat infectious diseases. Overall, current studies establish PNPs as versatile nanotherapeutics for drug targeting with strong potentials to improve the treatment of various diseases. Abstract : Platelet membrane–coated nanoparticles inherit biofunctions of natural platelets and are capable of adhering to various disease‐relevant substrates. They have become drug carriers exceptionally suitable for targeted drug delivery. Herein, the recent development of platelet‐mimicking nanoparticles with different structures for drug targeting to injured blood vessels, cancer cells, and drug‐resistant bacteria is reviewed.